Character Education from the Students’, Teachers’, and Schools’ Perspective - Hanafi Hanafi (Yayasan Visi Intan Permata, 2021)
In 2016, the Indonesian Government emphasized character education by sparking a Character Strengthening Program or Program Penguatan Karakter/PPK to build and strengthen the students’ character. This program focuses on character building but it mainly highlights five main good characters which are religiosity, nationalism, integrity, independence, and cooperation. This study aims to deeply understand the perspective of students, teachers, and schools toward knowledge and value of character education and to explore the linkage among them as a complete picture. A mixed-method research was employed in this study. The data was collected from 2 junior and 2 senior high schools, which involved 4 headmasters, 12 teachers, and 212 students. Regression analysis was performed to evaluate the roles of teachers and schools in the internalization of character education among students, while the qualitative approach was employed to understand teachers’ and schools' perspectives. This study finds that based on the students’ perspective, teachers' and schools' roles are playing a significant effect on the internalization of the values of character education to them. The school and the teachers were not familiar with terms used by the governments PPK programs. Despite, the school and teacher are in synergy in developing the students’ good character with their own character development terms such as “akhlaq mulia” which is actually has similar values with the Government’s Character Strengthening Program